Highly stable polymer coated nano-clustered silver plates: A multimodal optical contrast agent for biomedical imaging - Ray, Aniruddha (Nanotechnology, 2014)
Here we present a new optical contrast agent, based on silver nanoplate clusters embedded inside a polymer nano matrix. Unlike nanosphere clusters, which have been well studied, nanoplate clusters have unique properties due to the different possible orientations of interaction between the individual plates, resulting in a significant broadening of the absorption spectra. These nanoclusters were immobilized inside a polymer cladding, so as to maintain their stability and optical properties under in vivo conditions. The polymer coated silver nanoplate clusters show a lower toxicity, compared to the uncoated nanoparticles. At high nanoparticle concentrations, cell death occurs mostly due to apoptosis. These nanoparticles were used for targeted fluorescence imaging in a rat glioma cell line by incorporating a fluorescent dye into the matrix, followed by conjugation of a tumor targeting F3 peptide. We further used these nanoparticles as photoacoustic contrast agents in vivo, to enhance the contrast of the vasculature structures in a rat ear model. We observed a contrast enhancement of over 90%, following nanoparticle injection. It is also shown that these NP’s can serve as efficient contrast agents, with specific targeting abilities, for broadband multimodal imaging, usable for diagnostic applications and extendable into use as therapeutic agents as well.